2018
DOI: 10.1038/s41598-018-21795-y
|View full text |Cite
|
Sign up to set email alerts
|

GSK3 is a negative regulator of the thermogenic program in brown adipocytes

Abstract: Brown adipose tissue is a promising therapeutic target in metabolic disorders due to its ability to dissipate energy and improve systemic insulin sensitivity and glucose homeostasis. β-Adrenergic stimulation of brown adipocytes leads to an increase in oxygen consumption and induction of a thermogenic gene program that includes uncoupling protein 1 (Ucp1) and fibroblast growth factor 21 (Fgf21). In kinase inhibitor screens, we have identified glycogen synthase kinase 3 (GSK3) as a negative regulator of basal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 56 publications
(75 reference statements)
1
17
2
Order By: Relevance
“…GSK-3 activity was necessary throughout iTreg differentiation, as no inactive-phosphorylated GSK-3 was detected after 3 days of culturing naive CD4 + T cells in Treg media. The classical cAMP/PKA activity downstream of the β2-AR exists in tumor cells as well as adipocytes, suppressing GSK-3 activity (70,71). mice received A20 cells followed by allo-HCT with BM alone or with 2 × 10 5 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…GSK-3 activity was necessary throughout iTreg differentiation, as no inactive-phosphorylated GSK-3 was detected after 3 days of culturing naive CD4 + T cells in Treg media. The classical cAMP/PKA activity downstream of the β2-AR exists in tumor cells as well as adipocytes, suppressing GSK-3 activity (70,71). mice received A20 cells followed by allo-HCT with BM alone or with 2 × 10 5 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have indicated that small-molecule inhibitors of GSK3 have favorable metabolic effects in rodents, which exhibit some of the same metabolic effects as FGF21 administration, including improved glucose tolerance and prevention of diet-induced obesity [87][88][89][90]. One potential mechanism by which these agents could induce thermogenenic activation is by inhibitory phosphorylation of GSK3 in a PKA-dependent manner, which in turn result in enhanced activity of p38 MAPK signaling module [91]. In our study, we found treatment of differentiated brown adipocytes with indirubin (10 μM) indeed showed a modest inhibition of GSK3β by enhanced the phosphorylation of Ser-9 (p-GSK3β) (Ser9) in vitro (Supplymentary Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…This gene negatively regulates the Wnt pathway during lineage commitment towards adipogenesis in mouse embryonic stem cells. The gene product inhibits retinoic acid receptor β and negatively inhibits brown adipocyte programming [84,85]. Interestingly, cyclin D1 (Ccnd1), a cell cycle regulator that downregulates during the early phases of adipogenesis in mesenchymal stem cells [86], is downregulated specifically in treated cells in the current study.…”
Section: Discussionmentioning
confidence: 56%